Identification of persons, through complete prosthetic labeling - Gabriela Sánchez- Sandoval; Grillith Tucto-Travezaño; Jessica Figueroa-Contreras (Kiru)
The labelling of complete prostheses is important in therecognition of victims by natural or material disasters and inthe recognition of people with mental problems. At presentthere are different marking techniques that will be explainedin the present work. The objective of the review article is tomake known these techniques of marking completeprosthesis.